Penetapan Target Tata Kelola TI Berbasis Konteks untuk Organisasi Keagamaan Menggunakan Faktor Desain COBIT 2019 - Yoel Harmel Timothy Kumaat; Yohanes Andreas Robert Langi; Mahardika Inra Takaendengan; Winsy Christo Deilan Weku; Dodisutarma Lapihu; Stephano Caesar Wenston Ngangi (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2026)
This study evaluates the IT governance capability of the SIT GMIM integrated information system using the COBIT 2019 framework. SIT GMIM supports church data management and administration at synod, regional, and congregation levels but has never undergone a formal IT governance evaluation. Using a mixed-method descriptive case study design, data were collected through questionnaires, semi-structured interviews, direct observation, and document review from SIT GMIM managers at the central synod level. Capability levels were assessed for six DSS processes (DSS01–DSS06) and four MEA processes (MEA01–MEA04) using COBIT 2019 performance management guidelines, with gap analysis comparing current and target capability levels. The DSS domain achieved an average capability level of 1.17 (Level 1 – Performed Process), while the MEA domain achieved 0.75 (Level 1 – Performed Process). DSS02 reached Level 2 (Managed Process), while MEA04 remained at Level 0 (Incomplete Process). Gap analysis revealed DSS05 (Security Services) has the largest gap of 2 levels, while DSS03, DSS04, MEA02, MEA03, and MEA04 have gaps of 1 level. DSS01, DSS02, DSS06, and MEA01 achieved their targets. This study provides the first formal COBIT 2019 assessment of a church information system in Indonesia, establishing a baseline for IT governance improvement in religious organizations. Recommendations focus on documentation, incident logging, backup management, endpoint security, internal control evaluation, compliance monitoring, and assurance mechanisms